Genomic Diversity 1999
DOI: 10.1007/978-1-4615-4263-6_10
|View full text |Cite
|
Sign up to set email alerts
|

The Trans-Caucasus and the Expansion of the Caucasoid-Specific Human Mitochondrial DNA

Abstract: The topology of the network of western Eurasian mitochondrial DNA (mtDNA) lineage clusters in the context of their expansion and spread in this geographic area is analysed. Special attention is devoted to the inner nods of the reconstructed median network tree, ancestral to mtDNA lineage clusters H and V, to the Caucasus and TransCaucasus area populations and to the problem of timing of the expansion of the Caucasoid-specific mtDNA lineage clusters in western Europe versus in the Trans-Caucasus. It appears on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 13 publications
0
13
0
1
Order By: Relevance
“…Most of the derivatives of this cluster are found in the Near East, which is considered to be the place of origin of this haplogroup. Haplogroup HV is found in the Caucasus (Georgia, Armenia, and Osetia) at the frequency of about 8%, and at a lower frequency, in Europe, India, and Central Asia [24,30]. The Thus, analysis of mtDNA lineages in Oroks showed that this ethnic group is characterized by a unique set of mtDNA types, which distinguish this ethnic group from the Siberian populations, which are close to it linguistically and geographically.…”
Section: Resultsmentioning
confidence: 93%
“…Most of the derivatives of this cluster are found in the Near East, which is considered to be the place of origin of this haplogroup. Haplogroup HV is found in the Caucasus (Georgia, Armenia, and Osetia) at the frequency of about 8%, and at a lower frequency, in Europe, India, and Central Asia [24,30]. The Thus, analysis of mtDNA lineages in Oroks showed that this ethnic group is characterized by a unique set of mtDNA types, which distinguish this ethnic group from the Siberian populations, which are close to it linguistically and geographically.…”
Section: Resultsmentioning
confidence: 93%
“…Two additional clades join haplogroups J and T and haplogroups H, V and HV respectively. Derivatives of at least some of them are found in Europe, North Africa, Central Asia and even India, but the most probable origin for all these expansions is the Near East-Caucasus area [2,17,27]. Finally, cluster U seems to have suffered a radial spread (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…mtDNA analysis has been used extensively during the past 10 years, since the pioneering works of Vigilant (1990), Stoneking et al (1991), andVigilant et al (1991). Phylogeographic analysis of mtDNA lineages from all over the world has led to the identification of mtDNA haplogroups that are specific to either Africans, Europeans, or Asians/Amerindians (Torroni et al 1993(Torroni et al , 1994(Torroni et al , 1996(Torroni et al , 1998Chen et al 1995;Richards et al 1996;Watson et al 1997;Kivisild et al 1999aKivisild et al , 1999bMacaulay et al 1999;Metspalu et al 1999). Haplogroup allocation of a given mtDNA lineage allows the assessment of its (sub)continental origin, so that the matrilineal ancestry of admixed populations can be evaluated well (Torroni et al 1995;Bravi et al 1997;Green et al 2000;Rando et al 1999).…”
Section: Figurementioning
confidence: 99%